Kawasaki disease: what is the epidemiology telling us about the etiology? - Burgner, D; Harnden, A (2005)
Kawasaki disease (KD) is an important and common inflammatory vasculitis of early childhood with a striking predilection for the coronary arteries. It is the predominant cause of paediatric acquired heart disease in developed countries. Despite 40 years of research, the aetiology of KD remains unknown and consequently there is no diagnostic test and treatment is non-specific and sub-optimal. The consensus is that KD is due to one or more widely distributed infectious agent(s), which evoke an abnormal immunological response in genetically susceptible individuals. The epidemiology of KD has been extensively investigated in many populations and provides much of the supporting evidence for the consensus regarding etiology. These epidemiological data are reviewed here, in the context of the etiopathogenesis. It is suggested that these data provide additional clues regarding the cause of KD and may account for some of the continuing controversies in the field.